2020
DOI: 10.1080/24740527.2020.1768835
|View full text |Cite
|
Sign up to set email alerts
|

The lived experiences of chronic pain among immigrant Indian-Canadian women: A phenomenological analysis

Abstract: Background: Chronic pain is a growing public health concern affecting 1.5 million people in Canada. In particular, it is a concern among the expanding immigrant population, because immigrant groups report higher pain intensity than non-immigrants. In 2011, the Indian population became the largest visible minority group and continues to be the fastest growing. Though the prevalence of chronic pain among Canadian Indians is unknown, research has found a higher prevalence among Indian women than men in India, Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…14,28 We illustrate the point of transferability of qualitative findings using two articles in the Special Issue. 28,29 Using a qualitative descriptive methodology, Dale et al 28 interviewed recently discharged patients about their procedural oral pain experiences while mechanically ventilated in the intensive care unit (ICU). Using an object elicitation approach, the authors found that patients recalled significant pain and distress related to oral care in the ICU but that, because of ventilation, were unable to self-report this pain.…”
Section: Current Controversiesmentioning
confidence: 99%
See 4 more Smart Citations
“…14,28 We illustrate the point of transferability of qualitative findings using two articles in the Special Issue. 28,29 Using a qualitative descriptive methodology, Dale et al 28 interviewed recently discharged patients about their procedural oral pain experiences while mechanically ventilated in the intensive care unit (ICU). Using an object elicitation approach, the authors found that patients recalled significant pain and distress related to oral care in the ICU but that, because of ventilation, were unable to self-report this pain.…”
Section: Current Controversiesmentioning
confidence: 99%
“…The findings from this study are transferrable to the growing literature on the development of pain education frameworks in various disciplines such as medicine, nursing, and dentistry. [30][31][32] Similarly, Mustafa et al 29 explored the lived experience of chronic pain in immigrant Indian-Canadian women using a phenomenological design. The authors found that immigrant Indian-Canadian women's experiences of pain are influenced by several unique sociocultural factors (e.g., gender roles, work burden, lack of social support), which in turn impact pain expression, openness to treatment, and the consequences of pain on the family.…”
Section: Current Controversiesmentioning
confidence: 99%
See 3 more Smart Citations